Effects of CT Number Derived Matrix Density on Preferential Flow and Transport in a Macroporous Agricultural Soil. Issue 7 (2nd July 2015) - Katuwal, Sheela; Moldrup, Per; Lamandé, Mathieu; Tuller, Markus; de Jonge, Lis W.
Abstract : Preferential flow and transport in structured soils can be intimately linked to numerous environmental problems. Surface‐applied chemicals are susceptible to rapid transport to deeper depths in structural soil pores, thereby potentially contaminating valuable environmental resources and posing risks to public health. This study focused on establishing links between the structural pore space and preferential transport using a combination of standard physical measurement methods for air and water permeabilities, breakthrough experiments, and X‐ray computed tomography (CT) on large soil columns. Substantial structural heterogeneity that resulted in significant variations in flow and tracer transport was observed, despite the textural similarity of the investigated samples. Quantification of macropore characteristics with X‐ray CT was useful but not sufficient to explain the variability in air permeability, saturated hydraulic conductivity, and solute transport. This was due to the limited CT scan resolution and large structural variability below this resolution. However, CTmatrix, a new parameter derived from the CT number of the matrix excluding stones and large mostly air‐filled macropores, was found to be useful for determining the magnitude of preferential flow under boundary conditions of constant, near‐saturated flow.